Efektifitas Mind Mapping Dalam Pembelajaran Kosakata Bahasa Jepang Pada Pemelajar Tingkat Dasar - Ningrum, Rosita (Lingua Cultura, 2012)
Article clarified the research entitled ã€Œã€Œåˆç´šå¦ç¿’è€…ã«ãŠã‘ã‚‹æ—¥æœ¬èªžã®èªžå½™å¦ç¿’ã«ãŠã„ã¦ã®ãƒžã‚¤Â ãƒ³ãƒ‰ãƒ»ãƒžãƒƒãƒ”ãƒ³ã‚°ã®åŠ¹æžœã€which were translated as "The Effectiveness of Mind Mapping In JapaneseVocabulary Learning for A Basic Level Learners". In previous studies, mind mapping was tested on reading skill,Â but for this research it was focused on vocabulary with the assumption that the language learners usually gotÂ difficulties in learning both languages. Technique of mind mapping was tested on a two-semester student to findÂ out the effectiveness of its techniques in learning Japanese vocabulary. This research used experimental methods.Â This design involved two groups of subjects. One group, as experimental group, was given the mind mappingÂ learning technique, and the other group (the control group) was treated with the conventional learningÂ techniques. Data were taken in two ways, the quantitative method was using instrument in the forms of pre testÂ and post test on both sample class. The qualitative method applied interview to complete the descriptive dataÂ analysis. Then, the pre test and post test data were analyzed by measuring the normality of data and test-t toÂ know to what extent the effectiveness of mind mapping techniques was successfully applied to the sample. ToÂ strengthen those results, the outcomes of interview was transcribed to see the sampleâ€™s responses in line withÂ mind mapping techniques to the study of Japanese vocabulary. The research result indicates that mind mappingÂ technique is proven more effective in learning Japanese vocabulary compared to the conventional way.